2021
DOI: 10.1111/rssb.12442
|View full text |Cite
|
Sign up to set email alerts
|

Instrument Residual Estimator for Any Response Variable with Endogenous Binary Treatment

Abstract: The data and programs for this paper can be obtained, typing 'Myoung-jae Lee' in Google and clicking on 'Instrument Residual Estimator'. The programs are written in 'GAUSS'; a 2-week trial version is available freely at www.aptech.com. For some inverse-weighting estimators, a tuning constant τ to prevent division by 0 is needed; there is no single best τ, but τ = 0.001 or 0.01 are used. Also, to improve finite-sample performance of some estimators, an integer q = 0, 1, 2, … is chosen, where q is not a tuning c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 45 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…To this question, Lee (2018) showed that the OLS of y on d − π x ("OLS PSR ") is consistent for E{ω(x)µ 1 (x)} without the restrictive condition. Going further, Lee (2021) showed that when d is endogenous with a binary instrument z, the IVE of y on d with instrument z − ζ x ("IVE ISR "), where ζ x ≡ E(z|x) is the instrument score (IS), is consistent for a modified OW average of µ 1 (x).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To this question, Lee (2018) showed that the OLS of y on d − π x ("OLS PSR ") is consistent for E{ω(x)µ 1 (x)} without the restrictive condition. Going further, Lee (2021) showed that when d is endogenous with a binary instrument z, the IVE of y on d with instrument z − ζ x ("IVE ISR "), where ζ x ≡ E(z|x) is the instrument score (IS), is consistent for a modified OW average of µ 1 (x).…”
Section: Discussionmentioning
confidence: 99%
“…For exogenous d, Lee (2018) shows that the OLS of y on d − π x is consistent for E{ω(x)µ 1 (x)} for any form of y regardless of whether π x = λ x , as long as y 1 − y 0 makes sense. y 1 − y 0 makes sense for continuous, count, or binary y; for categorical y, turn each category to a dummy variable to use each dummy variable as an outcome.…”
Section: Ols With Ps Residualmentioning
confidence: 93%
See 2 more Smart Citations
“…To drop this condition, we propose the "subsample OLS" of Y on D−E(D|X, D = 0, d), which turns out to be consistent for the "overlapweight average" of µ d (X) as in Lee (2018Lee ( , 2021.…”
Section: Introductionmentioning
confidence: 99%